Unraveling Tumor Heterogeneity in an Apparently Monolithic Disease: BCL2 and Other Players in the Genetic Landscape of Nodal Follicular Lymphoma - Magnoli, Francesca; Tibiletti, Maria Grazia; Uccella, Silvia (Frontiers in Medicine, 2019)
Follicular lymphoma (FL) is the most common form of non Hodgkin lymphoma in Western countries. Although traditionally considered a well-defined, easy to diagnose lymphoproliferative disorder, in the last few years several forms of FL have been described, showing definite clinicopathological features and encompassing a variegated and complex genetic background. This has led to the inclusion of specific FL variants and separate entities in the latest update of the WHO classification. However, even in the context of classical FL, many aspects of intra- and inter-tumoral heterogeneity have been recognized, with major consequences on diagnosis and clinical management. This review focuses on genetic heterogeneity in classical FL, from precursors and early development to progression and transformation, in terms of both clonal heterogeneity and unusual genetic features. Several factors have been suggested to contribute to the broad spectrum of clinicopathological, phenotypic and genetic features observed in otherwise morphologically classical cases. Among them, deregulation of the epigenetic machinery and interactions with tumor microenvironment seem to play a pivotal role, together with genetic aberrations involving well known molecular pathways and mechanisms physiologically operating in the germinal center. In the era of personalized medicine, precision diagnostics based both on understanding of the complex interplay among all these factors and on novel developments will become crucial to predict the outcome and guide the treatment of FL patients.